2017
DOI: 10.1177/1010428317698356
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase lysine-specific demethylase-1–mediated epigenetic silence of KLF2 contributes to gastric cancer cell proliferation, migration, and invasion

Abstract: Gastric cancer is one of the most common malignancies and leading causes of cancer-related death worldwide. An increasing number of evidence has revealed that gastric tumorigenesis is a multistage pathological state, and epigenetic alterations are considered to play critical roles in the etiology of gastric cancer. Lysine-specific demethylase-1, a histone demethylase, has been linked to malignancy in several human cancers and considered to epigenetically regulate many tumor suppressor genes during tumorigenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It has been reported that KDM1A promoted cancer progression by removing methyl groups from the methylated histones H3 lysine 4 (H3K4) and H3 lysine 9 (H3K9) ( 37 ). KDM1A was overexpressed in various malignant tumors, including cervical cancer ( 38 ), esophageal cancer ( 39 ), ovarian cancer ( 40 ), and GC ( 41 ). The elevated KDM1A level was also related to tumor stage, histological grade, and lymph node metastasis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that KDM1A promoted cancer progression by removing methyl groups from the methylated histones H3 lysine 4 (H3K4) and H3 lysine 9 (H3K9) ( 37 ). KDM1A was overexpressed in various malignant tumors, including cervical cancer ( 38 ), esophageal cancer ( 39 ), ovarian cancer ( 40 ), and GC ( 41 ). The elevated KDM1A level was also related to tumor stage, histological grade, and lymph node metastasis ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lncRNA HOXA11‐AS Promotes Proliferation and Invasion of Gastric Cancer by Scaffolding the Chromatin Modification Factors PRC2, LSD1, and DNMT1 (Sun, Nie, et al, ); lincRNAFEZF1‐AS1 represses p21 expression to promote gastric cancer proliferation through LSD1‐Mediated H3K4me2 demethylation (Liu, Xia, et al, ); and lncRNA 00511 Acts as an Oncogene in Non‐small‐cell Lung Cancer by Binding to EZH2 and Suppressing p57 (Sun, Li, et al, ). KLF2, a tumor suppressor and the member of KLF family with Cys2/His2 zinc‐finger domains, is dysregulated in multiple cancers (Dimmeler et al, ; Fang, Xu, Lin, Xu, & Tian, ; Manavski et al, ). It has been demonstrated that EZH2 could directly bind to KLF2 promoter and silence of KLF2 expression result in the blocking of tumor suppressor features of KLF2 (Huang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Kruppel‐like factor 2 (KLF2), a tumor suppressor, is dysregulated in various cancers . Ma et al revealed that KLF2 was downregulated by LncRNA SNHG15 to promote pancreatic cancer proliferation .…”
Section: Discussionmentioning
confidence: 99%